2015
DOI: 10.1002/jmri.25094
|View full text |Cite
|
Sign up to set email alerts
|

How reader perception of capsule affects interpretation of washout in hypervascular liver nodules in patients at risk for hepatocellular carcinoma

Abstract: Reader perception of capsule affects interpretation of washout. This effect can influence nodule categorization using imaging-based diagnostic systems. J. Magn. Reson. Imaging 2016;43:1337-1345.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 39 publications
2
34
1
Order By: Relevance
“…Their results revealed that while quantitative assessment of washout showed better sensitivity than qualitative assessment, this improvement is obtained at the expense of a higher number of false-positive findings (74). A recent retrospective study by Sofue et al showed that a lesion-to-liver signal intensity ratio of 0.88 at MR imaging correlated most strongly with readers' visual interpretation of washout (68).…”
Section: Washout Appearancementioning
confidence: 91%
See 3 more Smart Citations
“…Their results revealed that while quantitative assessment of washout showed better sensitivity than qualitative assessment, this improvement is obtained at the expense of a higher number of false-positive findings (74). A recent retrospective study by Sofue et al showed that a lesion-to-liver signal intensity ratio of 0.88 at MR imaging correlated most strongly with readers' visual interpretation of washout (68).…”
Section: Washout Appearancementioning
confidence: 91%
“…A recent article has shown that, in some cases, the presence of a capsule creates the visual perception of washout, even when a mass is not hypointense to background liver (68). Because this was an unrecognized phenomenon until recently, some prior studies may have failed to distinguish washout appearance from the optical illusion of washout created by an enhancing capsule.…”
Section: Threshold Growthmentioning
confidence: 95%
See 2 more Smart Citations
“…Six prior studies have assessed reader agreement regarding LI-RADS categories (11,19,20) or major features of HCC (11,(19)(20)(21)(22). Unlike these studies, which all included readers from the same institution, ours is further enhanced by (a) multicenter international cross-sectional reader pool, including community practice, academic, and mixed practice environments; (b) derivation of the cases from eight different sites; (c) the largest number of readers tested to date; (d) no training module aside from the LI-RADS materials available online; (e) mixture of all LI-RADS 10% of total cases.…”
Section: Agreement On Major Featuresmentioning
confidence: 99%